Relationship between obesity and leptin serum among low socioeconomic primary school children aged 5-7 years - Soenarto Soenarto; Helena Anneke Sendow-Tangkilisan (Indonesian Pediatric Society, 2010)
Background Obesity has become a major health problem globally,Â indicates as an epidemic problem by World Health OrganizationÂ (WHO). Adiposity rebound period may represent critical periodÂ for the development of adiposity. Recent data suggest that, inÂ industrialized countries, people of low socioeconomic groupÂ are more likely to be obese than their high socioeconomicÂ counterparts. Level of serum leptin was reported to be higher inÂ obese subjects. There has been lack of data regarding leptin serumÂ level in Indonesian obese children.Objective This study aimed to investigate leptin serum level inÂ low socioeconomic obese children.Â Methods This was a cross sectional study perfonned in TumintingÂ District, Manado. Obesity was defined based on body mass indexÂ for Asiaô€‡Pacific condition, i.e., grade I obesity (BMI 25/29.9 kg/Â mL), grade II (BM] 30-40 kg/ml), and grade III (BM] > 40 kg/m2Â Low socioeconomic status was detennined based on Government'sÂ program Cash Direct Aid Program. loBod sample was obtainedÂ from inclusion subjects, consisted of leptin serum.Results Fiftyô€‡two low socioeconomic obese children were eligibleÂ lith age ranged between 5 to 7 years. They were divided intoÂ grade ] obesity (43 or 82.7%), and grade II (9 or 17.3%). TheÂ lowest leptin blood level was 10,291 pg/mL, while the highest wasÂ 41,500 pg/dL. All girls had nonnal serum leptin level; in contrastÂ all boys had increased serum leptin level.Â Conclusions Leprin level increased in those subjects whose BMIÂ increased.